Clinical Characteristics-Assisted Risk Stratification for Extent of Thyroidectomy in Patients With 1–4 cm Solitary Intrathyroidal Differentiated Thyroid Cancer - Dong, Fang; Zhou, Lin; Wang, Shuntao; Mao, Jinqian; Liu, Chunping; Shi, Wei (Frontiers in Endocrinology, 2022)
Background: Differentiated thyroid cancer (DTC) is the most common type of thyroid cancer. The 2015 American Thyroid Association (ATA) guidelines recommend that lobectomy is suitable for solitary intrathyroidal DTC (SI-DTC) of 1–4 cm. However, some SI-DTC patients with other high-risk characteristics still have a poor prognosis and require more aggressive surgical methods. This study aimed to explore the clinical characteristics that are important for the identification and treatment of high-risk patients with SI-DTC of 1-4 cm. Methods: The study cohort was obtained from the SEER database, consisting of data between 2004 and 2013. The outcome measures were thyroid carcinoma-specific mortality (CSM) and all-cause mortality(ACM). Patient survival curves were examined using Kaplan-Meier analyses with log-rank tests and Cox proportional hazards regression analyses. Hazard ratios (HRs) were used to show the magnitude of the effect of disease stage on DTC-specific patient mortality. Results: The study included 55,947 patients with SI-DTC of 1-4 cm and 4,765 patients with DTC>4 cm. Tumor size, surgical approach, age, sex, race, and radiation exposure were independent risk factors for CSM and ACM. SI-DTC patients with female, age≤45, and 1cm< tumor size≤2cm were at low risk of CSM [HR=0.014 (0.002-0.115)] and ACM [HR=0.115 (0.077-0.171)] when stratified by age, sex, and tumor size. Compared to T3 patients, CSM was not significantly different in male patients, age>45, 2cm45, 1cm